2017
DOI: 10.58397/ashkmdc.v22i3.126
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Consumption and Academic Performance among Medical Students of Dow University of Health Science (DUHS), Karachi, Pakistan

Abstract: Objective: To determine the frequency of caffeine consumption and  its  effect  on  academic  perfor-  mance among medical students of DUHS, Karachi, Pakistan. Methods: A cross-sectional study was conducted at Dow Medical College, DUHS. About 400 medical undergraduate students from first to final  year  MBBS  were  included  through  systematic  sampling.  Those students who were on leave on  the  day  of  interview  and  addicted  to  substance  abuse  other than caffeine and those who were on drug use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Consistent with our results on schoolchildren, Champlin and colleagues found that drinking CED was associated with a lower GPA even after controlling for potential confounding variables. Further in Pakistan, no relationship was found between the GPA and CED consumption among university students ( 50 ).…”
Section: Discussionmentioning
confidence: 94%
“…Consistent with our results on schoolchildren, Champlin and colleagues found that drinking CED was associated with a lower GPA even after controlling for potential confounding variables. Further in Pakistan, no relationship was found between the GPA and CED consumption among university students ( 50 ).…”
Section: Discussionmentioning
confidence: 94%
“…According to this study, prevalence of caffeine consumption in 1657 undergraduate medical students, from 1 st year to final year of MBBS, of Nishtar Medical University, Pakistan is 90.8 percent, which is in consonance with the fact that 80 percent of the population consumes caffeine regularly, and according to a study conducted among medical students at Dow University of Health Science (DUHS) in Karachi, Pakistan, 94 percent of students consume caffeine in any form such as tea or coffee. 2,15 In another research conducted at the University of the Balearic Islands, Spain it was found that 91.1 percent of their students consume caffeine. 16 The key finding of this study was that the PSQI scores increase with the increase in caffeine consumption.…”
Section: Discussionmentioning
confidence: 97%
“…Coffee and Caffeine products are helpful in cognitive performance, which is necessary for the academics of college students. Still, there is no significant relationship between academic performance and caffeine intake in college students (Khan et al, 2015); thus, caffeine intake does not enhance a student's academic performance but sharpens cognitive performance, which can benefit the learning environment.…”
Section: Review Of Related Literaturementioning
confidence: 98%